Desain Front-End Aplikasi Urban Store dengan Metode User Centered Design Menggunakan Flutter - Ammar Zuhair; Bayu Priyatna; Tukino Tukino (Jurnal Publikasi Teknik Informatika, 2025)
The rapid growth of e-commerce platform has increased the demand for mobile applications with attractive and user-friendly interfaces. This study focuses on designing anda developing the front-end of the Urban Store fashion application using the User Centered Design (UCD) approach and the Flutter . UCD is implemented to ensure that design process prioritizes user needs and preferences through the stages of planning, research, design, adaptation, and evaluation. The prototype was created using Figma, covering key features sush as login, homepage, checkout, profile pages. Implementation was carried out using Flutter and the Dart programming language interface evaluation was conducted using the System Usability Scale (SUS) method with 15 respondents, resulting in an average SUS score of 84,0, which falls into the “good” category. These results demonstrate that the UCD approach effectively produces a responsive and intuitive UI/UX design that aligns with user expectations. This research contributes to the development of user-experience -oriented intefaces for mobile-based e-commerce applications.